Comparison of Medical Device Calibration Compliance Between Paripurna and Utama Accredited Community Health Centers in Palu City - Alhabsyi, Manal; Suarayasa, Ketut; Rahman, Abd (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Compliance with medical equipment calibration is essential to ensure service quality and patient safety. However, not all medical devices in community health centers (Puskesmas) in Palu City have been calibrated according to standards. Objective: This study aimed to analyze differences in calibration compliance between Paripurna-accredited and Utama-accredited Puskesmas. Methods: A comparative quasi-experimental study with a posttest-only design was conducted at Kamonji and Lere Health Centers from August to September 2025. Total sampling was applied to all employees, yielding 127 respondents. Data were analyzed using the Independent Sample t-test. Results and Discussion: Kamonji Health Center showed higher instrumental compliance, while Lere Health Center demonstrated slightly higher normative compliance. Statistical analysis indicated a significant difference in calibration compliance between the two health centers (t = 2.726; p = 0.007). Conclusion: Calibration compliance was significantly higher at the Paripurna-accredited health center, suggesting that higher accreditation status is associated with better calibration practices. Strengthening supervision and documentation is recommended, particularly for Utama-accredited health centers.